Statistical Methods for Analyzing Economic Impacts of Climate Change - Taha, Reem Talal; Abed, Mohammed Qadoury; Alamro, Loai; Muhsin, Aseel Ibraheem (Journal of Ecohumanism, 2024)
Background: The economic consequences of climate change are deep and varied, affecting worldwide economies by changing agricultural output, health results, and infrastructure strength. Measuring these effects necessitates strong statistical techniques to offer precise and useful information. Objective: This article seeks to examine the financial repercussions of climate change through the use of sophisticated statistical techniques, addressing both the direct and indirect economic consequences. The study aims to pinpoint key economic sectors impacted and give numerical predictions of potential monetary damages. Methods: We used a wide-ranging data set from 1990 to 2020 to evaluate the economic effects of climate change through the use of multiple regression analysis, time-series forecasting, and econometric modeling. Important factors consist of GDP, agricultural production, healthcare expenditures, and costs associated with disasters. Also, Monte Carlo simulations as well to assess the variability of our forecasts. Results: The analysis shows that by 2050, climate change might cause a yearly decrease of around 2% in global GDP, amounting to a possible loss of 2.5 trillion. It is anticipated that agricultural productivity will decrease by 8%, leading to an annual loss of 150 billion. Healthcare expenses linked to illnesses caused by climate change could rise by 12%, leading to an extra 200 billion in spending. Projected to increase by 20%, disaster-related costs are expected to grow by an additional 250 billion, increasing the annual economic burden. Conclusion: The results emphasize the considerable financial impact of climate change, underscoring the immediate necessity for mitigation tactics. It is important for policymakers to place a high importance on climate resilience in order to reduce these economic losses. The statistical techniques used create a strong foundation for future studies and policy-making regarding the economic effects of climate change.